P399 Higher anti-tumour necrosis factor-alpha drug levels are associated with improved radiological outcomes in patients with perianal fistulising Crohn's disease: A retrospective multi-centre study. (27th May 2021) - De Gregorio, M; Lee, T; Krishnaprasad, K; Amos, G; An, Y K; Bastian-Jordan, M; Begun, J; Borok, N; Brown, D J M; Cheung, W; Connor, S; Gerstenmaier, J; et al.
Abstract: Background: Higher anti-tumour necrosis factor-α (TNF) drug levels are associated with improved clinical fistula healing and closure in perianal fistulising Crohn's disease (pfCD). It is hypothesised that higher drug levels will lead to improved healing on magnetic resonance imaging (MRI); but this is yet to be established. This study evaluated the association between anti-TNF drug levels and radiological outcomes in pfCD. Methods: A multi-centre retrospective study (FISCAL), across 10 ANZ Inflammatory Bowel Disease Consortium sites. Patients with pfCD on stable maintenance dosing of infliximab or adalimumab, with drug levels within 6-months of a pelvic MRI from 2010 to 2020 were included. Patients receiving perianal fistula surgery between drug level and MRI were excluded. MRI disease activity was scored using the Van Assche Index (VAI), with an inflammatory sub-score (VAIinfl ) derived from the VAI indices: hyperintensity on T2-weighted images, collections >3mm diameter, and rectal wall involvement. Primary endpoint was radiological healing (VAIinfl ≤6). Secondary endpoint was radiological remission (VAIinfl =0). Drug level tertiles were correlated to changes in VAIinfl scores. ROC analyses were used to identify optimal target drug levels. Results: Of 193 patients (infliximab, n =117; adalimumab, n =76), radiological healing was achieved in 47.0 and 44.7% and radiological remission in 17.1 and 15.8% of patients receiving infliximab and adalimumab, respectively. Patients with radiological healing had higher median drug levels compared to those with radiologically active disease (infliximab 6.0 vs 3.9µg/mL, P =0.03; adalimumab 9.1 vs 6.2µg/mL, P =0.02). Patients with radiological remission had higher median drug levels compared to those with radiologically active disease (infliximab 7.4 vs 3.9µg/mL, P <0.01; adalimumab 9.8 vs 6.2µg/mL, P =0.07). There was a significant incremental reduction in median VAIinfl with higher anti-TNF drug level tertiles, shown in Figure 1. By ROC analyses, the optimal trough infliximab levels for radiological healing and remission were 4.0µg/mL (sensitivity 69.1%, specificity 45.2%, AUC 0.62, P =0.03) and 6.5µg/mL (sensitivity 60.0%, specificity 72.2%, AUC 0.67, P =0.02), respectively. The optimal adalimumab levels for radiological healing and remission were 7.2µg/mL (sensitivity 67.6%, specificity 59.5%, AUC 0.65, P =0.03) and 9.7µg/mL (sensitivity 58.0%, specificity 70.0%, AUC 0.62, P =0.20), respectively. Conclusion: In the largest study of its kind, higher anti-TNF drug levels were associated with improved MRI parameters as per the VAI in patients with pfCD; with an incremental improvement in MRI outcomes at higher anti-TNF drug level tertiles for both infliximab and adalimumab. Replication in prospective studies are awaited.